Risk Chart for Future Mortality and Ischaemic Events Following Peripheral Bypass Surgery. Issue 1 (July 2015) - Wisman, P.P.; van Hattum, E.S.; van der Graaf, Y.; de Borst, G.J.; Tangelder, M.J.D.; Moll, F.L.
Abstract : Objectives: A prediction model to identify determinants and quantify the risk of future ischaemic events in patients with peripheral arterial disease (PAD) provides a personal risk profile to offer individualized patient care. A risk chart was derived and validated in patients who received infrainguinal bypass surgery. Methods: The Bypass Oral anticoagulants or Aspirin Risk Chart (BOA-RC2) was based on a pre-defined subgroup of the Dutch BOA trial ( N  = 482), the derivation cohort. The primary outcome event for BOA-RC2 was the composite of all cause death, non-fatal myocardial infarction, or non-fatal ischaemic stroke during a 10 year follow up. Determinants and long-term risk were identified with multivariate Cox regression analyses. Validation of the BOA-RC2 was performed in the remaining patients of the complete BOA trial cohort ( N  = 2, 650 − 482 = 2, 168), the validation cohort. Results: The primary outcome event occurred in 67% (321/454) of the derivation cohort and in 66% (1, 371/2, 083) of the validation cohort during a median follow up of 6.6 years. The BOA-RC2 included the following determinants: age, critical limb ischaemia, diabetes, and a prior vascular intervention. The performance of the BOA-RC2 was good with a Brier score of 0.19, an area under the curve of 0.73, and a Hosmer–Lemeshow statistic of p  = .9. Conclusions: The BOA-RC2 proves to be fit for the prediction of mortality and major ischaemic events in patients after peripheral bypass surgery. The BOA-RC2 can be used to adequately inform the patient about his/her risk of future events in an illustrative manner and stress the necessity of preventative measures, such as lifestyle adjustments, screening for risk factors, and drug treatments. In the future, the BOA-RC2 may be of interest to identify patients at high risk of mortality and ischaemic events for clinical research on new therapeutic options.